Epidemiological characteristics of P. vivax asymptomatic infections in the Peruvian Amazon - Villasis, Elizabeth; Garcia Castillo, Stefano S.; Guzman, Mitchel; Torres, Julian; Gomez, Joaquin; Garro, Katherine; Cordova, Ana Maria; Reategui, Carolina; Abanto, Caroline; Vinetz, Joseph; Gamboa, Dionicia; Torres, Katherine (Frontiers in Cellular and Infection Microbiology, 2022)
Introduction Herein, we tested the hypothesis that Asymptomatic P. vivax (Pv) infected individuals (Asym) feature different epidemiological, clinical and biochemical characteristics, as well as hematological parameters, potentially predictive of clinical immunity in comparison to symptomatic Pv infected individuals (Sym). Methodology Between 2018 - 2021, we conducted 11 population screenings (PS, Day 0 (D0)) in 13 different riverine communities around Iquitos city, in the Peruvian Amazon, to identify Pv Sym and Asym individuals. A group of these individuals agreed to participate in a nested case - control study to evaluate biochemical and hematological parameters. Pv Asym individuals did not present common malaria symptoms (fever, headache, and chills), had a positive/negative microscopy result, a positive qPCR result, reported no history of antimalarial treatment during the last month, and were followed-up weekly until Day 21 (D21). Control individuals, had a negative malaria microscopy and qPCR result, no history of antimalarial treatment or malaria infections during the last three years, and no history of comorbidities or chronic infections. Results From the 2159 individuals screened during PS, data revealed a low but heterogeneous Pv prevalence across the communities (11.4%), where most infections were Asym (66.7%) and submicroscopic (82.9%). A total of 29 Asym, 49 Sym, and 30 control individuals participated in the nested case - control study (n=78). Ten of the individuals that were initially Asym at D0, experienced malaria symptoms during follow up and therefore, were included in the Sym group. 29 individuals remained Asym throughout all follow-ups. High levels of eosinophils were found in Asym individuals in comparison to Sym and controls. Conclusion For the first-time, key epidemiological, hematological, and biochemical features are reported from Pv Asym infections from the Peruvian Amazon. These results should be considered for the design and reshaping of malaria control measures as the country moves toward malaria elimination.